The Role of the Nuclear Envelope Protein MAN1 in Mesenchymal Stem Cell Differentiation. Issue 12 (31st July 2017) - Bermeo, Sandra; Al‐Saedi, Ahmed; Kassem, Moustapha; Vidal, Christopher; Duque, Gustavo
ABSTRACT: Mutations in MAN1, a protein of the nuclear envelope, cause bone phenotypes characterized by hyperostosis. The mechanism of this pro‐osteogenic phenotype remains unknown. We increased and decreased MAN1 expression in mesenchymal stem cells (MSC) upon which standard osteogenic and adipogenic differentiation were performed. MAN1 knockdown increased osteogenesis and mineralization. In contrast, osteogenesis remained stable upon MAN1 overexpression. Regarding a mechanism, we found that low levels of MAN1 facilitated the nuclear accumulation of regulatory smads and smads‐related complexes, with a concurrently high expression of nuclear β‐Catenin. In addition, we found adipogenesis to be decreased in both conditions, although predominantly affected by MAN1 overexpression. Finally, lamin A, a protein of the nuclear envelope that regulates MSC differentiation, was unaffected by changes in MAN1. In conclusion, our studies demonstrated that lower levels of MAN1 in differentiating MSC are associated with higher osteogenesis and lower adipogenesis. High levels of MAN1 only affected adipogenesis. These effects could have an important role in the understanding of the role of the proteins of the nuclear envelope in bone formation. J. Cell. Biochem. 118: 4425–4435, 2017. © 2017 Wiley Periodicals, Inc. Abstract : Mutations in MAN1, a protein of the nuclear envelope, cause bone phenotypes characterized by hyperostosis. The mechanism of this pro‐osteogenic phenotype remains unknown. We increased and decreased MAN1 expression in mesenchymal stem cells (MSC) upon which standard osteogenic and adipogenic differentiation were performed. Our studies demonstrated that lower levels of MAN1 in differentiating MSC are associated with higher osteogenesis and lower adipogenesis. High levels of MAN1 only affected adipogenesis. These effects could have an important role in the understanding of the role of the proteins of the nuclear envelope in bone formation.